The relationship between neuropsychological tests of visuospatial function and lobar cortical thickness. Issue 5 (28th May 2018) - Zink, Davor N.; Miller, Justin B.; Caldwell, Jessica Z. K.; Bird, Christopher; Banks, Sarah J.
ABSTRACT: Introduction : Tests of visuospatial function are often administered in comprehensive neuropsychological evaluations. These tests are generally considered assays of parietal lobe function; however, the neural correlates of these tests, using modern imaging techniques, are not well understood. In the current study we investigated the relationship between three commonly used tests of visuospatial function and lobar cortical thickness in each hemisphere. Method : Data from 374 patients who underwent a neuropsychological evaluation and MRI scans in an outpatient dementia clinic were included in the analysis. We examined the relationships between cortical thickness, as assessed with Freesurfer, and performance on three tests: Judgment of Line Orientation (JoLO), Block Design (BD) from the Fourth edition of the Wechsler Adult Intelligence Scale, and Brief Visuospatial Memory Test-Revised Copy Trial (BVMT–R-C) in patients who showed overall average performance on these tasks. Using a series of multiple regression models, we assessed which lobe's overall cortical thickness best predicted test performance. Results : Among the individual lobes, JoLO performance was best predicted by cortical thickness in the right temporal lobe. BD performance was best predicted by cortical thickness in the right parietal lobe, and BVMT–R-C performance was best predicted by cortical thickness in the left parietal lobe. Conclusions : Performance on constructional tests of visuospatial function appears to correspond best with underlying cortical thickness of the parietal lobes, while performance on visuospatial judgment tests appears to correspond best to temporal lobe thickness. Future research using voxel-wise and connectivity techniques and including more diverse samples will help further understanding of the regions and networks involved in visuospatial tests.